Feasibility of Learner Autonomy Oriented Physics Learning Material to Train Student's Science Process Skills - Elsa Zakiati; Mastuang Mastuang; Suyidno Suyidno (Program Studi Pendidikan Fisika FKIP Universitas Lambung Mangkurat, 2019)
Low level of student's science process skills is due to the lack of use of experiments in learning. The study was conducted to produce learning materials which oriented to valid, practical, and effective learner autonomy; so that it is feasible to train student' science process skills. The research uses the ADDIE development model design including Analyze, Design, Develop, Implement, and Evaluate. The research subjects were 30 students of class X B TKJ in one of vocational high school at Banjarmasin. The research instrument used a validation sheet, observation sheet from the lesson plan, observation sheet of science process skills, and test the learning outcomes of students. Further data were analyzed descriptively qualitatively and quantitatively. The results showed: 1) learning materials which oriented to learner autonomy were valid because the lessons plan, teaching material, student worksheet, and learning outcomes test were in the valid category, 2) learning materials which oriented to learner autonomy including practical because the component of lessons plans with direct instruction, guide inquiry and cooperative learning type group investigation in very practical categories, 3) learning materials which oriented to learner autonomy is effective because the cognitive N-gain tests are 0.51 in the medium category; 4) observations of science process skills in good categories and the result of N-gain science process skills tests are 0.76 in the high category. It can be concluded that the learning materials which oriented to learner autonomy were feasible to practice science process skills vocational high school's students.